2019
DOI: 10.1021/acschembio.9b01019
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Small Molecule Probe of Rpn-6, an Essential Subunit of the 26S Proteasome

Abstract: A considerable number of essential cellular proteins have no catalytic activity and serve instead as structural components to aid in assembling protein complexes. For example, the assembly and function of the 26S proteasome, the major enzymatic complex necessary for ubiquitin-dependent protein degradation, require a number of essential protein contacts to associate the 19S regulatory particle with the 20S core particle. Previously, small molecule inhibitors of the active sites of the 20S core particle have bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, this mode of action has not been experimentally confirmed yet. Another small molecule (TXS-8) has recently been discovered which binds to RPN6 and disrupts 26S proteasome assembly (Tian & Trader, 2020). This probe might represent an interesting scaffold to develop further peptoid inhibitors that interfere with 19S/20S assembly.…”
Section: Inhibition Of Proteasome Super-complexesmentioning
confidence: 99%
“…However, this mode of action has not been experimentally confirmed yet. Another small molecule (TXS-8) has recently been discovered which binds to RPN6 and disrupts 26S proteasome assembly (Tian & Trader, 2020). This probe might represent an interesting scaffold to develop further peptoid inhibitors that interfere with 19S/20S assembly.…”
Section: Inhibition Of Proteasome Super-complexesmentioning
confidence: 99%
“…26S proteasome non-ATPase regulatory subunit 11­(PSMD11), also known as Rpn6, is one of the essential proteins that promotes 26S proteasome assembly and plays a vital role in the association between the 19S regulatory particle (RP) and the 20S core particle (CS). Previous studies have revealed that Rpn6 was a potential druggable target which blocked protein degradation by interfering with the complete assembly of 26S . Therefore, it was presumed that these 1,2,4-oxadiazole derivatives activated Nrf2 pathway and exhibited anti-inflammatory activity by interfering with the 26S assembly and blocking the degradation of ubiquitinated Nrf2 in 26S proteasome.…”
Section: Results and Discussionmentioning
confidence: 99%
“…HSP90 activity is usually part of the final step to promote protein folding, assembly of multiprotein complexes, and binding of ligands to substrates (Abildgaard et al, 2020;Jakob et al, 1995;Karagöz et al, 2014). As a subunit of RP, RPN6 is an important component of the 26S proteasome and has been identified as a molecular tweezer that fixes CP and RP together to form a fully activated 26S proteasome (Cho et al, 2015;Estrin et al, 2013;Isono et al, 2005;Pathare et al, 2012;Santamaria et al, 2003;Tian and Trader, 2020). Specifically, RPN6 interacts with RPT6 of RP and the α2 subunit of CP (Chen et al, 2016;Tian and Trader, 2020).…”
Section: Loss Of Function Of Hsp906 Reduces 26s Proteasome Activity A...mentioning
confidence: 99%
“…As a subunit of RP, RPN6 is an important component of the 26S proteasome and has been identified as a molecular tweezer that fixes CP and RP together to form a fully activated 26S proteasome (Cho et al, 2015;Estrin et al, 2013;Isono et al, 2005;Pathare et al, 2012;Santamaria et al, 2003;Tian and Trader, 2020). Specifically, RPN6 interacts with RPT6 of RP and the α2 subunit of CP (Chen et al, 2016;Tian and Trader, 2020). PBD2 (PRC2) is a subunit of CP and is responsible for endowing active sites with chymotrypsin cleavage properties and maintaining the degradation activity of the 26S proteasome (Arendt and Hochstrasser, 1997;Dick et al, 1998;Heinemeyer et al, 1997;Kisselev et al, 1999Kisselev et al, , 2003Kumar Deshmukh et al, 2019;Marshall and Vierstra, 2019).…”
Section: Loss Of Function Of Hsp906 Reduces 26s Proteasome Activity A...mentioning
confidence: 99%